Catalytic chelation technique for the removal of lead in mangifera indica and musa acuminata fruits - Nuraqila Ismaili; Fakulti Sains (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Sains (Kimia)) - Universiti Teknologi Malaysia, 2018